Two 22q telomere deletions serendipitously detected by FISH. Issue 11 (November 1998) - Precht, K S; Lese, C M; Spiro, R P; Huttenlocher, P R; Johnston, K M; Baker, J C; Christian, S L; Kittikamron, K; Ledbetter, D H
Abstract : Cryptic telomere deletions have been proposed to be a significant cause of idiopathic mental retardation. We present two unrelated subjects, with normal G banding analysis, in whom 22q telomere deletions were serendipitously detected at two different institutions using fluorescence in situ hybridisation (FISH). Both probands presented with several of the previously described features associated with 22q deletions, including hypotonia, developmental delay, and absence of speech. Our two cases increase the total number of reported 22q telomere deletions to 19, the majority of which were identified by cytogenetic banding analysis. With the limited sensitivity of routine cytogenetic studies (approximately 2-5 Mb), these two new cases suggest that the actual prevalence of 22q telomere deletions may be higher than currently documented. Of additional interest is the phenotypic overlap with Angelman syndrome (AS) as it raises the possibility of a 22q deletion in patients in whom AS has been ruled out. The use of telomeric probes as diagnostic reagents would be useful in determining an accurate prevalence of chromosome 22q deletions and could result in a significantly higher detection rate of subtelomeric rearrangements.